Cinnamon Bark Polyphenol Extract on Abdominal Adipose Tissue Dynamics in Growing Broilers - Tayam, S.; Erdogan, S. (Facta - Fundacao Apoio Ciencia & Tecnologia Animal, 2025)
This study investigates the impact of cinnamon bark polyphenols (CBP) on adipogenesis in broiler chickens across developmental stages. A total of 288 one-day-old male broilers were fed for 42 days with a basal diet or diets supplemented with 300 mg/kg (CBP300) and 600 mg/kg (CBP600) of CBP extract. CBP supplementation significantly reduced body weight gain and feed intake compared to the control group (p<0.05). This reduction indicates that CBP regulates energy metabolism, thereby enhancing metabolic efficiency and consequently preventing excessive fat accumulation. Abdominal fat proportion increased with age, and CBP notably influenced tissue weight. The addition of CBP reduced adipocyte sizes compared to the control group. Serum triglycerides decreased, whereas insulin and leptin levels rose significantly (p<0.05). Moreover, the elevated expression of PPAR gamma and LPL genes in adipose tissue highlights their involvement in adipogenesis and lipid metabolism regulation. This upregulation is beneficial, as it enhances lipid metabolism efficiency, contributing to the reduction in abdominal fat accumulation observed in CBP-supplemented groups. These data suggest that CBP plays a relevant role in balancing lipogenesis
Keywords: Broilers; Lipid Metabolism; Lpl; Polyphenol; Ppar Gamma